Study on the Effect of Different Fe2O3/ZrO2 Ratio on the Properties of Silicate Glass Fibers - Jianxun Liu; Jianping Yang; Haibin Huo; Liang Lei; Ying Cui; Zhishen Wu (Advances in Materials Science and Engineering)
A series of silicate glass fibers with different ratios of Fe2O3/ZrO2 were prepared, and their corrosion resistance, mass loss, and strength loss were characterized. The crystallization and melting properties of the fibers were analyzed by differential scanning calorimetry (DSC), high temperature viscometer, and high temperature microscope. The results show that the deformation temperature, sphere temperature, hemisphere temperature, and crystallization temperature of the fiber initially decrease and then increase with the increase of Fe2O3/ZrO2 ratio, while the molding temperature decreases with the increase of the ratio of Fe2O3/ZrO2. When the ratio is close to 1 : 1, its alkali resistance is almost same as that of AR-glass fiber, and the drawing process performance is better. However, with the increase of the ratio, its alkali resistance continues to decline and the poor wire drawing performance is not conducive to the drawing operation.